Prevalence of Metabolic Syndrome in Ischemic Heart Disease Patients (Journal of Dhaka Medical College, 2015)
Ischemic heart disease (IHD) is one of the four leading causes of death globally. An important risk factor for IHD is metabolic syndrome. The definition of metabolic syndrome is not universally agreed. The most commonly used definition was proposed by the National Cholesterol Education Program Adult Treatment panel III ( NCEPATP III ), where metabolic syndrome defined as involving three or more of the following criteria: Blood pressure > 130/85 mm of Hg, fasting blood sugar > 100 mg / dl, triglyceride level > 150mg / dl, high density lipoprotein cholesterol ( HDL-C) < 40mg / dl in men and < 50mg/ dl in women, and abdominal circumference > 102 cm in men and > 88 cm in women.I- which is characterized by clustering of central obesity, hypertension, hyperglycemia and dyslipidemia. This cross sectional analytical study was carried out in the Department of Biochemistry, Dhaka Medical college. The samples were collected from the Department of Cardiology of Dhaka Medical College Hospital (DMCH), Bangladesh Institute of Research on Diabetes Endocrine and Metabolic Disorder (BIRDEM), and National Institute of Cardiovascular Diseases (NICVD), Dhaka, during the period from July 2009 to June 2010. Age distribution of study group shows that majority of the IHD patients with or without metabolic syndrome were in 41-60 years of age group. In the present study the prevalence of metabolic syndrome in IHD patients was found to be 30%. Prevalence was higher in less then 50 years of age group. The prevalence was also higher in female than male.J Dhaka Medical College, Vol. 23, No.2, October, 2014, Page 157-160